(untitled) (Revista Apotheke, 2021)
This text covers research on Cassandra Rios (1932), a lesbian and Lesbian writer of greater notoriety for Brazil. The context of most of his literary production took place during a dictatorial period, in which his works suffered severe censorship and persecution. The direction of this production, seeks to reflect part of the work “I am a lesbian” (1980), written in a serial, with several editions after this one. In the work, Flávia recognizes her gender identity by revisiting her past and transcribing it in a narrative tone, as well as everything that involved and involves being a lesbian woman, such as veiled violence until today. The theme of female homosexuality becomes the core of this whole process, in which Cassandra’s life and work demonstrate fundamental artistic-social relevance. Considerations are also presented regarding the author’s non-autobiographical biographical writing, which, through her productions, reveals her perspective regarding not only being a woman, but also her lesbian experience.